Communigram: Faster Projects and Processes Through Engineered and Controlled Communication - Brown, Kenneth; Korczak, Jerzy; Schmied, Helwig (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
In this paper we present a novel approach to accelerating projects and processes by organizing and controlling the necessary flows of communication in a so-called "Communigram". After a short introduction to the state of the art in this field of management both in terms of available methodologies and IT tools, we expose how the Communigram is used to define the communication flows of a project or process. We then describe the main characteristics of the software components that have been developed to simplify the use of the Communigram and provide additional value to its users in terms of time savings, comfort, and motivation. Drawing upon real-life implementations of the approach using the new software tools, we discuss the advantages as well as the limitations and give an outlook as to where we believe future evolutions will be directed.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 9-29